Top-down attention does not modulate mechanical hypersensitivity consecutive to central sensitization: insights from an experimental analysis - Della Porta, Delia; Scheirman, Eléonore; Legrain, Valéry (Pain (Amsterdam), 2024)
We found no evidence for an effect of high working memory load on the development of secondary hypersensitivity-a proxy of central sensitization. AbstractAccording to the neurocognitive model of attention to pain, when the attentional resources invested in a task unrelated to pain are high, limited cognitive resources can be directed toward the pain. This is supported by experimental studies showing that diverting people's attention away from acute pain leads to experiencing less pain. Theoretical work has suggested that this phenomenon may present a top-down modulatory mechanism for persistent pain as well. However, conclusive empirical evidence is lacking. To fill this gap, we used a preregistered, double-blind, between-subject study design to investigate whether performing a tailored, demanding, and engaging working memory task unrelated to pain (difficult) vs a task that requires less mental effort to be performed (easy), could lead to lower development of secondary hypersensitivity-a hallmark of central sensitization. Eighty-five healthy volunteers, randomly assigned to one of the 2 conditions, performed a visual task with a different cognitive load (difficult vs easy), while secondary hypersensitivity was induced on their nondominant forearm using high-frequency stimulation. To assess the development of secondary hypersensitivity, sensitivity to mechanical stimuli was measured 3 times: T0, for baseline and 20 (T1) and 40 (T2) minutes after the procedure. We did not observe any significant difference in the development of secondary hypersensitivity between the 2 groups, neither in terms of the intensity of mechanical sensitivity nor its spatial extent. Our results suggest that a top-down modulation through attention might not be sufficient to affect pain sensitization and the development of secondary hypersensitivity.